2017
DOI: 10.1038/s41598-017-17255-8
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Fcγ-receptor engagement by a hexameric Fc-fusion protein triggers Fcγ-receptor internalisation and modulation of Fcγ-receptor functions

Abstract: Engagement of Fcγ-receptors triggers a range of downstream signalling events resulting in a diverse array of immune functions. As a result, blockade of Fc-mediated function is an important strategy for the control of several autoimmune and inflammatory conditions. We have generated a hexameric-Fc fusion protein (hexameric-Fc) and tested the consequences of multi-valent Fcγ-receptor engagement in in vitro and in vivo systems. In vitro engagement of hexameric-Fc with FcγRs showed complex binding interactions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 51 publications
5
60
1
Order By: Relevance
“…In vitro studies demonstrated that GL-2045 bound with high avidity to all of the canonical FcγRs, inhibited the binding of ICs from patients with RA to FcγR-expressing CHO cells, blocked ADCP and ADCC, and induced signaling through FcγRIIa and FcγRIIIa. These findings are consistent with recent reports demonstrating that recombinant human IgG1 hexamers and hexamers of IgG4, containing the IgG1 CH3 domain with or without specific point mutations, inhibit select FcγR engagement and block complement activation (40,41). Collectively, these data suggest that GL-2045 may be reproducibly generated as a drug product with target-specific functional activity -attributes that made it suitable for characterization in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro studies demonstrated that GL-2045 bound with high avidity to all of the canonical FcγRs, inhibited the binding of ICs from patients with RA to FcγR-expressing CHO cells, blocked ADCP and ADCC, and induced signaling through FcγRIIa and FcγRIIIa. These findings are consistent with recent reports demonstrating that recombinant human IgG1 hexamers and hexamers of IgG4, containing the IgG1 CH3 domain with or without specific point mutations, inhibit select FcγR engagement and block complement activation (40,41). Collectively, these data suggest that GL-2045 may be reproducibly generated as a drug product with target-specific functional activity -attributes that made it suitable for characterization in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…2A). This finding is in line with recent reports on other multimeric Fc molecules such as the Stradomer (17), hexameric Fc (21,22), and Fc3Y (20). Ortiz et al (20) established that structures with more than three Fc fragments led to Syk and ERK phosphorylation; furthermore, a trimeric lead molecule (Fc3Y) did not activate but, on the contrary, potently inhibited immune complex-mediated effector cell activation.…”
Section: Discussionsupporting
confidence: 85%
“…A trivalent molecule termed Fc3Y showed protection in mouse models of ITP, arthritis, and epidermolysis bullosa acquisita (20). Finally, a hexameric Fc molecule showed increased binding to FcgRs and dendritic cell-specific intercellular adhesion molecule-3 grabbing nonintegrin, appeared to fully activate complement (C1q binding and C5b-9 deposition) (21), and effectively interfered with FcgR function (22). Ab hexamer structures are reported to have superior complement fixing properties; indeed, upon binding to cell-surface Ags, IgG monomers spontaneously arranged into ordered hexamer structures that recruited and activated C1 (23).…”
mentioning
confidence: 99%
“…The hexamer also induced endocytosis of fluorescently tagged Fc receptors in macrophages and in cynomolgus monkeys. This work has implications for the treatment of Fc receptor mediated autoimmune diseases …”
Section: Multivalency In Cell Signalingmentioning
confidence: 99%
“…Fc Receptor signaling plays several important roles in the immune system such as triggering phagocytosis, cytokine release, and antigen presentation. Qureshi et al . generated hexameric Fc γ fusions linked by the IgM tail piece.…”
Section: Multivalency In Cell Signalingmentioning
confidence: 99%